Present and future habitat suitability for fishing cat (Prionailurus viverrinus) in Thailand - Noowong, Jedsada; Paansri, Paanwaris; Suksavate, Warong; Chaiyes, Aingorn; Pattanakiat, Sura; Nakmuenwai, Pisut; Duengkae, Prateep (Agriculture and Natural Resources, 2024)
Importance of the work: The fishing cat (Prionailurus viverrinus Bennett, 1833) is a poorly studied wildcat that inhabits floodplains and wetlands. It is threatened throughout its entire range and has even been extirpated in some locales due to human-driven habitat loss. Objectives: To use the maximum entropy algorithm to assess the environmental factors and the present and future habitat suitability for fishing cats in Thailand. Materials and Methods: Occurrence data (2007–2022) were used from 28 areas in the published literature and unpublished data to develop habitat suitability models. Results: Key variables influencing fishing cat habitat suitability were identified: mean diurnal range of temperature, annual precipitation, topographic wetness index and elevation. The analysis identified areas of highly suitable habitat totaling 1,237 km2 outside and 64 km2 (approximately 5%) within six protected areas. These findings emphasized the importance of conserving both protected and nonprotected land to support fishing cat populations, especially in the provinces of Phetchaburi, Prachuap Khiri Khan, Samut Sakhon, Samut Prakan and Samut Songkhram. Projections indicated that the area of suitable habitat would rebound in the 2050s and 2070s, but with large decreases within protected areas to even less area than at present (approximately 40%), due to climate change. Main finding: These results underscored the need for proactive conservation measures in the face of ongoing environmental changes and for conservation outside protected areas. Urgent actions are required to implement effective management strategies and policies that address habitat loss and secure the long-term survival of this vulnerable species.